Atrophy of the optic chiasm is associated with microvascular diabetic complications in type 1 diabetes - Tarkkonen, Aleksi; Claesson, Tor-Björn; Eriksson, Marika I.; Forsblom, Carol; Thorn, Lena M.; Summanen, Paula; Groop, Per-Henrik; Putaala, Jukka; Gordin, Daniel; Martola, Juha (Frontiers in Endocrinology, 2023)
Abstract Introduction Diabetic neuropathy and diabetic eye disease are well known complications of type 1 diabetes. We hypothesized that chronic hyperglycemia also damages the optic tract, which can be measured using routine magnetic resonance imaging. Our aim was to compare morphological differences in the optic tract between individuals with type 1 diabetes and healthy control subjects. Associations between optic tract atrophy and metabolic measures, cerebrovascular and microvascular diabetic complications were further studied among individuals with type 1 diabetes. Methods We included 188 subjects with type 1 diabetes and 30 healthy controls, all recruited as part of the Finnish Diabetic Nephropathy Study. All participants underwent a clinical examination, biochemical work-up, and brain magnetic resonance imaging (MRI). Two different raters manually measured the optic tract. Results The coronal area of the optic chiasm was smaller among those with type 1 diabetes compared to non-diabetic controls (median area 24.7 [21.0-28.5] vs 30.0 [26.7-33.3] mm2, p<0.001). In participants with type 1 diabetes, a smaller chiasmatic area was associated with duration of diabetes, glycated hemoglobin, and body mass index. Diabetic eye disease, kidney disease, neuropathy and the presence of cerebral microbleeds (CMBs) in brain MRI were associated with smaller chiasmatic size (p<0.05 for all). Conclusions Individuals with type 1 diabetes had smaller optic chiasms than healthy controls, suggesting that diabetic neurodegenerative changes extend to the optic nerve tract. This hypothesis was further supported by the association of smaller chiasm with chronic hyperglycemia, duration of diabetes, diabetic microvascular complications, as well as and CMBs in individuals with type 1 diabetes.